Antioxidant response to titanium dioxide nanoparticles by Saccharomyces cerevisiae grown in different carbon sources and heat-shock conditions - Capela-Pires, J (2004)
The physicochemical properties that make nanomaterials unique, also equip them with potential for affect environment adversely, causing oxidative injuries in the living beings. However, organisms also had to develop antioxidant defences to protect their cells from reactive oxygen species (ROS). Failure in the cell antioxidant defences, due to the contact with xenobiotic, results in stress causing oxidatives damages leading to loss of cell viability. Yeasts can contribute to understand the toxicity of titanium dioxide nanoparticles (TiO2-NP), because its cell structure and functional organization, share similarities with mammalians. Since the response of yeast to NPs can be influenced by temperature and available carbon source, the aim of this study was to evaluate the antioxidant response of Saccharomyces cerevisiae, grown in presence of glycerol with addition of 2% glucose and 5 g/mlTiO2-NP, in heat-shock conditionsTiO2-NP (size <100 nm) stock suspensions were prepared by sonication. Bioassays were performed in YEPG medium (1% yeast extract, 2% peptone, 3% glycerol). Culture flasks were inoculated with wild-type Saccharomyces cerevisiae UE-ME3 and shaken 150 rpm, at 28°C. At exponential phase was added glucose and TiO2-NP stock solution (YEPGD-NP) to obtain a final concentration of 2% and 5 lg/ml. Yeasts grown 200 min at 28 or 40°C (heat-shock, HS). Flasks lacking glucose (YEPG) or NPs served as controls. Biomass was quantified by dry weight. Post-12000 g supernatants were used for determination of GSH, GSSG and ROS contents by fluorescence as well as glutathione reductase (GR), glutathione peroxidase (GPx), glucose-6-phosphate dehydrogenase (G6PD), catalase (CTT1) activity by spectrophotometry. Post-12000 g pellets were used for determination of catalase (CTA1) activity. Statistical analysis by ANOVA I and Duncan test. The results showed that biomass,ROS level and GR activity in the cells grown in YEPGD were higher than those detected in cells grown in YEPG. Furthermore, cells grown in YEPGD exhibited lower levels of GSH and MDA and CTT1activity comparatively with yeasts grown in YEPG. S. cerevisiae grown in YEPGD-NP in HS showed growth inhibition to levels near of cells which used glycerol as carbon source. Additionally, it was also detected a decrease in the GSH contents, GSH/GSSG ratio, GPx, CTT1 and CTA1 activities as well as an increase in ROS content and GR activeity, relatively to the cells growing only in glycerol. It was also observed an increase in ROS level and GR activity in the yeast grown in YEPGD-NP, relatively to S. cerevisiae grown in YEPGD. TiO2-NP in HS caused oxidative stress in yeast grown in presence of glycerol and glucose, decreasing GSH/GSSG ratio,increasing ROS content and GR activity.